2017
DOI: 10.1523/jneurosci.2385-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Drp1 Ameliorates Synaptic Depression, Aβ Deposition, and Cognitive Impairment in an Alzheimer's Disease Model

Abstract: Excessive mitochondrial fission is a prominent early event and contributes to mitochondrial dysfunction, synaptic failure, and neuronal cell death in the progression of Alzheimer's disease (AD). However, it remains to be determined whether inhibition of excessive mitochondrial fission is beneficial in mammal models of AD. To determine whether dynamin-related protein 1 (Drp1), a key regulator of mitochondrial fragmentation, can be a disease-modifying therapeutic target for AD, we examined the effects of Drp1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
165
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 202 publications
(187 citation statements)
references
References 59 publications
8
165
0
1
Order By: Relevance
“…Importantly, mdivi-1 treatment markedly decreased extracellular amyloid deposition, prevented the development of cognitive deficits in Y-maze test and improved synaptic parameters, supporting the notion that abnormal mitochondrial dynamics plays an early and causal role in mitochondrial dysfunction and AD-related pathological and cognitive impairments in vivo [72,73]. These results suggest that neuropathology and combined cognitive decline can be attributed to hyperactivation of Drp1p (responsible for mitochondrial fragmentation) in the pathogenesis of AD and that inhibiting excessive Drp1p-mediated mitochondrial fission may be a new efficient therapeutic strategy for AD.…”
Section: Mitochondrial Dysfunction In Adsupporting
confidence: 55%
See 2 more Smart Citations
“…Importantly, mdivi-1 treatment markedly decreased extracellular amyloid deposition, prevented the development of cognitive deficits in Y-maze test and improved synaptic parameters, supporting the notion that abnormal mitochondrial dynamics plays an early and causal role in mitochondrial dysfunction and AD-related pathological and cognitive impairments in vivo [72,73]. These results suggest that neuropathology and combined cognitive decline can be attributed to hyperactivation of Drp1p (responsible for mitochondrial fragmentation) in the pathogenesis of AD and that inhibiting excessive Drp1p-mediated mitochondrial fission may be a new efficient therapeutic strategy for AD.…”
Section: Mitochondrial Dysfunction In Adsupporting
confidence: 55%
“…Treatment by mdivi-1, a mitochondrial fission inhibitor, rescued the mitochondrial fragmentation and distribution deficits and improve mitochondrial function in the Aβ-treated [72] and CRND8 [73] neurons both in vitro and in vivo. Importantly, mdivi-1 treatment markedly decreased extracellular amyloid deposition, prevented the development of cognitive deficits in Y-maze test and improved synaptic parameters, supporting the notion that abnormal mitochondrial dynamics plays an early and causal role in mitochondrial dysfunction and AD-related pathological and cognitive impairments in vivo [72,73].…”
Section: Mitochondrial Dysfunction In Admentioning
confidence: 96%
See 1 more Smart Citation
“…Further, our in vitro studies revealed that Mdivi1 is protective against Aβ-induced excessive mitochondrial fragmentation and mitochondrial dysfunction in AD neurons [47]. Several recent mouse model studies of AD, also revealed that Mdivi1 is protective against Aβ-induced synaptic and mitochondrial toxicities, particularly Mdivi1 reduces excessive mitochondrial fragmentation [5354]. Very little is known about synergistic protective effects of SS31 and Mdivi1 in AD neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies also reported that mitochondria-targeted molecules and mitochondrial division inhibitors reduce Aβ levels and mitochondrial and synaptic toxicities in AD neurons [47,53,54]. However, there are no published reports that investigated using combined treatments of mitochondria-targeted molecules and mitochondrial division inhibitors.…”
Section: Discussionmentioning
confidence: 99%